Proceedings of the 22nd Conference of the Computer-Human Interaction Special Interest Group of Australia on Computer-Human Inte 2010
DOI: 10.1145/1952222.1952259
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cognitive ageing on use of complex interfaces

Abstract: This paper discusses an experiment investigating the effects of cognitive ageing and prior-experience with technology on using complex interfaces intuitively. Overall 37 participants, between the ages of 18 to 83, participated in this study. All participants were assessed for their cognitive abilities and prior-experience with technology. It was anticipated that the Central Executive function (a component of Working Memory) would emerge as one of the important cognitive functions in using complex interfaces. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…This decision was based on observing the increasing use of touch-based interfaces for consumer products. The mediator interface for this experiment was designed based on research [29,30] that suggested that there was a significant negative correlation between visuospatial sketchpad capacity and time to complete the task and the number of errors. The number of controls in the mediator product for this experiment was kept at 5, to keep it within the visuospatial sketchpad capacity of an average older participant [31,32] .…”
Section: Stai Questionnairementioning
confidence: 99%
“…This decision was based on observing the increasing use of touch-based interfaces for consumer products. The mediator interface for this experiment was designed based on research [29,30] that suggested that there was a significant negative correlation between visuospatial sketchpad capacity and time to complete the task and the number of errors. The number of controls in the mediator product for this experiment was kept at 5, to keep it within the visuospatial sketchpad capacity of an average older participant [31,32] .…”
Section: Stai Questionnairementioning
confidence: 99%
“…Another related study is a series of works by Blackler et al (2010aBlackler et al ( , 2010b, Lawry et al (2010) and Reddy et al (2010) who empirically evaluated the major effects of cognitive abilities and technology familiarity on the intuitiveness of interaction with electronic devices. However, they focused on the factors of user age and prior experience, and the appearance of the products while not addressing the physicality.…”
Section: Related Workmentioning
confidence: 99%
“…These are application-specific, invisible, inseparable and integrated parts of real-life objects normally performing real-time functionalities (Jozwiak et al, 2010;Malinowski and Hao, 2011;Reddy et al, 2010). Their number, types and functionalities are escalating rapidly while their size is decreasing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations